Forum theatre as a participatory communication space for dialogue, collaboraton and solidarity - Kunt, Zeynep Feriha Eren (İstanbul Bilgi Üniversitesi, 2018)
This research explores Augusto Boal’s Forum Theatre as a participatory communication space. As an interactive form of performance, forum theatre is practiced with the communities experiencing various forms of oppression. As a methodology, forum theatre provides communities with the participatory tools for dialogue, collaboration and a space to develop potential strategies to understand and overcome their oppressions. This study explores the potential of forum theatre as a model for participatory action research by focusing on its reciprocal roles: to reveal social knowledge and start a process for transformation both in individual and collective levels. The discussion is drawn from the fieldwork conducted with a group of doctors who voluntarily came together forming a forum theatre group to develop strategies for maintaining the practices of the good medicine. The three-month long forum theater sessions with the doctors have led to the play called The Dr Good Physician, performed by the doctors for the audience who were colleagues/ “spectactors”. The audience members became spect-actors by acting out the solution strategies presented on stage. The research investigates all stages of forum theatre in terms of its participatory processes through this fieldwork. It is argued that forum theatre presents as a model of participatory communication and action research by “minimising the hierarchy” imposed on participants and maximising the possibility for “becoming active citizens” in life.

Bu tez, Augusto Boal’ın Forum Tiyatrosu metodolojisini katılımcı iletişim alanı olarak incelemektedir. İnteraktif bir performans biçimi olarak, yaşamlarında herhangi bir baskıyla karşıkarşıya olan topluluklarla çalışmalarda yaygın olarak uygulanan forum tiyatrosu topluluklara, diyalog, birlikte hareket etme ve baskıya karşı strateji geliştirilmesi için katılımcı araçlar sunar. Araştırma metodolojisi ve araştırma konusu olmanın kesişiminde yer alan tiyatro pratiği için örnek oluşturan bu çalışma, forum tiyatrosu süreçlerini, aynı zamanda katılımcı medya ve katılımcı eylem araştırması modeli olarak inceliyor. Tezin saha araştırmasını, iyi hekimlik pratiğini korumak üzere stratejiler geliştirmek için bir araya gelen doktorların oluşturduğu forum tiyatrosu oluşturdu. Doktorlarla üç ay süren forum tiyatrosu çalışmasının sonunda “Dr İyi Hekim” forum tiyatrosu hazırlandı. Doktorlar, oyunu, meslekdaşlarından oluşan bir izleyicioyuncu (spect-actor) grubu için oynadı. Forum bölümünde ise izleyiciler, sahnede kendi çözüm stratejilerini oynayarak izleyici-oyuncu oldu. Çalışma bu saha araştırması üzerinden forum tiyatrosunun bütün aşamalarını katılımcı süreçler açısından incelemektedir. Forum tiyatrosunun hiyerarşiyi en aza indirgeyen katılımcı iletişim ve eylem araştırması modeli olarak sunduğu olanaklar “aktif yurttaş” kavramıyla bağlantılı olarak tartışılmaktadır.
Diyalog, birlikte düşünme ve dayanışma için katılımcı iletişim alanı olarak forum tiyatrosu
Keywords: Augusto Boal; Forum Theatre; Participatory Media; Health System; Participatory Action Research; Augusto Boal; Forum Tiyatrosu; Katılımcı Medya; Sağlık Sistemi; Katılımcı Eylem Araştırması